The Added Effects of Rice Husk Ash Against to Growth and Yield on Basil (Ocimum basilicum) - Oktaviant, Dimas Panji; Purbajanti, Endang Dwi; Budiyanto, Susilo (Journal of Tropical Crop Science and Technology, 2019)
Basil is a spice plant that is widely used as a culinary additive, fragrance, atractan, and anti-bacterial because it produces essential oils, basil oil. This research aimed to identifying the affect of adding rice husk ash on different basil’s cultivars on growth and yield of basil (Ocimum basilicum). This research use 4 x 2 factorial experiment pattern with Completely Randomized Design consisting of 5 replication. The first treatment was various type of basil’s cultivars such as Genovese cultivars (K1) and Dark Opal cultivars (K2). The second treatment was doses of rice husk ash such as control or without giving rice husk ash (M0), 30 g/pot (M1), 35 g/pot (M2), dan 40 g/pot (M3).  The observed parameters were soil bulk density and porosity, plant height, leaves total, roots length, and leaves simplisia. The results showed that the application of husk ash can affect the increase in physical properties of the soil, but has not directly affected the growth parameters and yield of leaf simplisia. Dark Opal cultivars on all growth parameters showed higher yields, but Genovese cultivars showed higher yields or simplisia.